Female Teenagers as Sex-Workers: Their Reasons and Adaptive Mechanism - Suyanto, Bagong (Makara Human Behavior Studies in Asia, 2014)
This study attempts to assess and understand the exploitations of girls who are forced into prostitution in the sex industry through critical theory perspective. The study was conducted in Surabaya and in a touristic area Tretes, Pasuruan. Overall, the in-depth interviews were conducted to 45 informants, girls who are forced into prostitution, former young prostitutes, pimps, and also male customers. The study found that it takes more than just pressures of poverty, lack of education, and inadequate access to the labor market for young girls to be involved in the prostitution. In fact, their involvements is the impact of the life style and permissive behavior in dating, victims of dating rape, child abuse, broken home family, as well as victims of fraudulent practices and mode of recruitments that related to the increased market demand for new and young prostitutes, and also the peer groups’ influences which offer shortcuts to overcome problems and life pressures. As children who experienced commodifications in the commercial sex industry, the girls who are forced into prostitution generally undergo exploitation and social alienation process.